2019
DOI: 10.1111/jfb.14126
|View full text |Cite
|
Sign up to set email alerts
|

Membrane and calcium clock mechanisms contribute variably as a function of temperature to setting cardiac pacemaker rate in zebrafish Danio rerio

Abstract: Here, we show that heart rate in zebrafish Danio rerio is dependent upon two pacemaking mechanisms and it possesses a limited ability to reset the cardiac pacemaker with temperature acclimation. Electrocardiogram recordings, taken from individual, anaesthetised zebrafish that had been acclimated to 18, 23 or 28°C were used to follow the response of maximum heart rate (fHmax) to acute warming from 18°C until signs of cardiac failure appeared (up to c. 40°C). Because fHmax was similar across the acclimation grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
3
6
0
Order By: Relevance
“…Past studies also support the importance of RyR and intracellular Ca 2+ cycling for zebrafish SAN automaticity shown in our study, as ryanodine (intraperitoneal injection of 50 ng/g), combined with thapsigargin (1.3 µg/g, to block SR Ca 2+ reuptake) reduced HR by ∼40% (Marchant and Farrell, 2019). A similar result has been shown in another teleost (the trout), in which ryanodine (10 µM) and thapsigargin (1 µM) resulted in a 44% decrease in HR (Haverinen and Vornanen, 2007).…”
Section: Cellular Mechanisms Of Sinoatrial Node Automaticitysupporting
confidence: 90%
See 1 more Smart Citation
“…Past studies also support the importance of RyR and intracellular Ca 2+ cycling for zebrafish SAN automaticity shown in our study, as ryanodine (intraperitoneal injection of 50 ng/g), combined with thapsigargin (1.3 µg/g, to block SR Ca 2+ reuptake) reduced HR by ∼40% (Marchant and Farrell, 2019). A similar result has been shown in another teleost (the trout), in which ryanodine (10 µM) and thapsigargin (1 µM) resulted in a 44% decrease in HR (Haverinen and Vornanen, 2007).…”
Section: Cellular Mechanisms Of Sinoatrial Node Automaticitysupporting
confidence: 90%
“…The first indication of the currents involved in zebrafish SAN automaticity came from the discovery of a mutation (slow mo) that caused a reduction in HR by affecting a hyperpolarisation-activated inward current with similar properties to I f (Baker et al, 1997;Warren et al, 2001). More recently, the general involvement of the membrane and Ca 2+ "clocks" in SAN automaticity were investigated using pharmacological interventions, which confirmed the role of I f (block of HCN channels reduced HR by ∼65%) and demonstrated a role for intracellular Ca 2+ cycling (block of SR Ca 2+ release with ryanodine, combined with block of SR Ca 2+ reuptake with thapsigargin reduced HR by ∼40%) (Marchant and Farrell, 2019). Yet, the potential involvement of other membrane and Ca 2+ "clock" mechanisms (i.e., I Ca , T , I Ca , L ) and the relative importance of these two pacemaker systems for SAN automaticity in the zebrafish has not been explored.…”
Section: Zebrafish As a Model For Studies Of Sinoatrial Node Functionmentioning
confidence: 94%
“…At present, the mechanism(s) mediating this effect in fish is/are not completely understood. However, Marchant and Farrell ( 2019 ) recently showed that the pacemaker cells of the heart have both membrane and calcium “clocks,” and suggest that the latter is involved in the control of heart rate with changes in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first in fishes to examine the mRNA expression of components of the calcium and the membrane clock in SAN tissue. Both clocks are hypothesised to drive spontaneous depolarisation of pacemaker cells in the SAN in mammals, and evidence exists that this may (Hassinen et al, 2017;Marchant and Farrell, 2019), or may not be the case in fishes (Wilson and Farrell, 2013). Therefore, the differentially higher expression of HCN1, a membrane clock component, observed in the SAN compared with the atrial tissues is of significant interest.…”
Section: Discussionmentioning
confidence: 99%